Nontoxic Multinodular Goitre and Incidental Thyroid Cancer: What Is the Best Surgical Strategy?—A Retrospective Study of 2032 Patients - Krzysztof Kaliszewski; Beata Wojtczak; Jędrzej Grzegrzółka; Jacob Bronowicki; Sawsan Saeid; Bartłomiej Knychalski; Zdzisław Forkasiewicz (International Journal of Endocrinology)
Objectives. A discussion with regard to the most optimal surgical procedure in nontoxic multinodular goitre (NTMNG). We assessed and compared three main types of operations in 2032 patients with NTMNG. Methods. This is a retrospective study of 2032 patients operated on in one center due to NTMNG. The observation period was 48 to 120 months (mean and SD: 87 ± 20). Results. The early complications included uni- and bilateral recurrent laryngeal nerve paralysis (URLNP, BRLNP), overt tetany (OT), and postoperative bleeding (POB). We observed after TT, STT, and DO URLNP: 15 (1.73%), 3 (0.64%), and 2 (0.28%), respectively (p<0.05); BRLNP: 3 (0.34%), 2 (0.43%), and 0 (0.0%), respectively (p=0.25); OT: 42 (4.84%), 6 (1.29%), and 9 (1.28%), respectively (p<0.0001); and POB: 11 (1.26%), 4 (0.86%), and 3 (0.42%), respectively (p=0.209). Persistent complications we observed after TT, STT, and DO are the following: URLNP: 9 (1.03%), 3 (0.64%), and 1 (0.14%), respectively (p=0.086); BRLNP: 1 (0.11%), 1 (0.21%), and 0 (0.0%), respectively (p=0.51); and OT: 11 (1.26%), 2 (0.43%), and 2 (0.28%), respectively (p=0.052). Incidental thyroid cancer (ITC) was recognized after TT, STT, and DO in 18 (2.07%), 21 (4.52%), and 11 (1.56%), respectively (p=0.039). Recurrent goitre (RG) was observed in 1 (0.11%) after TT, 3 (0.64%) after STT, and 2 (0.28%) after DO (p=0.234). Conclusions. Performing less radical surgery in NTMNG is associated with a significantly lower risk of early and late URLNP and OT. In the case of BRLNP (early and persistent) and POB, no statistically significant differences are seen. The occurrence of ITC is higher following more radical surgeries. Less radical surgery is connected with a higher risk of RG.